PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI 5 TONJA DENPASAR TAHUN PELAJARAN 2025/2026 - Ni Kade Rahayu Antari; I Gusti Ngurah Triyana; I Gede Angga Supriana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Make A Match type cooperative learning model is a learning model that emphasizes students’ activeness in finding matching pairs of question and answer cards, thereby improving conceptual understanding and learning interaction. The low learning outcomes in Pancasila Education among fifth-grade students at SD Negeri 5 Tonja Denpasar form the background of this study. The purpose of this research is to determine the effect of the Make A Match type cooperative learning model on students’ Pancasila Education learning outcomes. The theories used in this study are cooperative learning theory and learning outcomes theory. This research employed a quantitative method with an experimental design. The population consisted of all fifth-grade students of SD Negeri 5 Tonja Denpasar using a saturated sampling technique. The sample included class VA consisting of 32 students as the experimental class and class VB consisting of 32 students as the control class. Class VA was treated using the Make A Match cooperative learning model, while class VB used conventional learning methods. Data were collected through observation, tests, and documentation, and analyzed using descriptive analysis and inferential statistical tests (independent sample t-test). The results showed that the significance value (2-tailed) was less than 0.05, so H0 was rejected and H1 was accepted, indicating a significant effect of the Make A Match cooperative learning model on the Pancasila Education learning outcomes of fifth-grade students at SD Negeri 5 Tonja Denpasar for the 2025/2026 school year.